"Suprascapular canal": Anatomical and topographical description and its clinical implication in entrapment syndrome - Al-Redouan, Azzat; Holding, Keiv; Kachlik, David (Annals of anatomy, 2021)
BACKGROUND: Suprascapular nerve (SN) entrapment syndrome accounts for 1-2% of all shoulder pain. The SN travels within a space between the suprascapular notch (SSN) and the spinoglenoid notch (SGN). PURPOSE: To report a detailed topographical study of the suprascapular canal (SSC) and ultimately sort the different types of SN entrapment by its anatomical localization within the canal. BASIC PROCEDURES: Observational study on 30 free dissected limbs of formaldehyde-fixed cadavers. The SN and vessels were traced as they passed through the SSC and the boundaries of the SSC were observed and documented. The SSC was then exposed by reflecting away the bordering muscles. Dimensions of the SSC as well as parameters of the SSN and SGN were measured using a digital caliper. Finally, a thorough literature review was made to survey the SN entrapment occurrence by site. MAIN FINDINGS: The SSC is situated in the spinoglenoid fossa, has an average width of 13 mm, and runs underneath the supraspinatus muscle with an average distance of 25 mm between the SSN and SGN sloping in an infero-postero-lateral direction. The first segment represents the SSC entrance site and is composed of two spaces: osteofibrous and musculofibrous. The second segment is bordered by the supraspinatus muscle fascia, lateral margin of the supraspinous fossa, glenohumeral joint capsule, and the bony surface of the scapula (spinoglenoid fossa). This represents the SSC passage site. The third segment represents the SSC exit site around the spinoacromial arch at the SGN. PRINCIPAL CONCLUSIONS: The SSC is defined as an osteofibrous canal running between the SSN and SGN enclosed by the supraspinatus fascia. It is anatomically composed of three segments: an entrance, a passage, and an exit. The distal SN passes through the SSC via five intervals that correspond to five potential sites of anatomical nerve entrapment: at the pre-entrance site, entrance site, passage site, exit site, and post-exit site. Each of those sites was found to be associated with specific causes and forms of entrapment.
Keywords: Rotator Cuff; Cadaver; lopatka; Shoulder Joint; Humans; ramenní kloub; Scapula; rotátorová manžeta; Nerve Compression Syndromes; mrtvola; lidé; úžinové syndromy